Optical spectroscopy of an A-type star / Khairul Hamizi Khairul Anuar - Khairul Anuar, Khairul Hamizi (2008)
In this research, the researcher performs the astronomical spectroscopy of an A-type star by using the 20-inch telescope, CCD and spectrograph at Langkawi National Observatory. The researcher chose A-type stars such as Sirius and Vega. The researcher successfully obtained absorption lines spectrum of the A-type star at 3 different exposure times. From the analysis of the A-type star spectrum, the results show only one Hydrogen Balmer lines that is Ha and one oxygen absorption lines for both star (Sirius and Vega). The analysis also shows that the radial velocity of Sirius was 6.604 x 103 m/s for 10s exposure time, 5.518 x 103 m/s (for 20s) and 6.604 x 103 m/s (for 30s). Its means that the star was moving away from earth. For the Vega, the radial velocity was -15.484 x 103 m/s at 40s exposure time and it means the star was moving toward earth. The error in obtaining the spectra was reduced by lowering the CCD's temperature, subtracting the dark current and flat fielding the image obtained.